Analisis Hadis Lā Dharara Walā Dhirāran sebagai Dasar Fatwa Keharaman Rokok - Rizki Fathul Anwar Sabani (Jurnal Penelitian Ilmu Ushuluddin, 2022)
This research is motivated by the views of the pros and cons of cigarette consumption in Indonesia. This study aims to analyze the hadith la dharara wala dhiraran which is the basis for the fatwa on the prohibition of smoking. This study applies a qualitative approach through the takhrij and syarah hadith methods as well as a comparative analysis of the views of the scholars. The results showed that the hadith la dharara wala dhiraran was found in the history of Ibn Majah No. 2340. It is known that this hadith is of authentic quality so that it can be used as a reference for Muslims. To mediate the pros and cons, the hadith related to the harm of cigarettes needs to be seen proportionally whether there are reasons that give the value of being haram or even only reaching exceptions, such as the prohibition of smoking for certain people and also the causes and effects of consuming it. This study concludes that the arguments cited as fatwas by various Islamic organizations do not refer directly to the smoking law, so the hadith cannot be used as a justification for the prohibition of smoking. Moreover, cigarettes have beneficial implications for economic growth and social welfare of the Indonesian people.